White House special handbook : how to rule the world in the 21st century - Kryzhanovskiĭ, M. (Mikhail), 1958- (New York : Algora Pub., 2007)
Here is the book that guides the president of the United States from the first day in the Oval Office to the day he or she walks out for the last time. In fact, the strategies and mindset recommended in these pages are essential tools for capturing the presidency as much as wielding it. The international scene today is either a madhouse or the product of extraordinarily cynical techniques such as these, applied with cold cunning, by our nations leaders. This manual outlines some of the resources, strategies and mechanisms at their disposal and some of the concerns and countervailing concerns that the Commander-in-chief needs to have in mind. This handbook provides a comparison of the world's premier intelligence agencies, discusses tactics of surveillance, war and public persuasion; and it gives practical advice on political maneuvering at the local, national and international levels. A rational, results-based handbook, it is destined to be a secret favorite of politicians, agents of the special services, C.E.O.s and corporate boards and everyone else who needs to be "ready to lead." And for the many other ambitious contenders in the world of winner-take-all bare-knuckles capitalism. The author, who cites decades of insider knowledge at both the K.G.B. and the C.I.A., says he originally compiled this book upon a request from Washington anonymous, of course
Introduction -- Political management at the top -- Electability -- The fight for the presidency -- Meet the electorate: basic information and the 2004 election state by state -- Campaign planning -- Iowa, New Hampshire: farm problems, energy costs, trade issues -- Who voted for whom in the 2004 presidential election -- Controlling the White House -- Domestic policy -- Managing the US Congress -- Foreign policy -- Managing spies at the top -- Which service is the best -- Techniques of special influence -- Surveillance -- How to run agents (secret sources) -- FBI helpers -- Identifying spies -- Strategies -- Presidential security -- Managing the military -- Commander-in-chief -- Strategy and tactics -- Learning from the past -- Learning from past presidents -- Where does the CIA fit in -- Happened to them? -- About the author.
Print version record.
English.
eBooks on EBSCOhost
Keywords: USA -- Präsident; USA -- Präsident.; Elections -- United States; Politics, Practical -- United States; Intelligence service -- United States; United States -- Politics and government; United States -- Foreign relations; États-Unis -- Politique et gouvernement; États-Unis -- Relations extérieures.; POLITICAL SCIENCE -- Public Affairs & Administration; POLITICAL SCIENCE -- Government -- Executive Branch; Elections; Intelligence service; Diplomatic relations; Politics and government; Politics, Practical; United States; Politik; Geheimdienst